Measurement of Pain Intensity and Evaluation of Analgesic Use in Post-Operative Patients in a Territory Care Hospital - V, Anaswara; Nair, Sujith S; Sivaprasad, Aswathy; Joy, Priyan; Nath, Vivek V (Journal of Pharmacy Practice and Community Medicine)
Aim: The aim of study is to measure pain intensity using pain scale in post-surgical patients and to evaluate the analgesics prescribed to them for the pain relief. Materials and Methods: A prospective observational study of six month duration was conducted. All the data were documented, analysed and frequency and percentage be used to summarize the result obtained. Data collected were entered into Microsoft Excel and Statistical analysis was done by using Microsoft Excel. Results: 96 patients (41 males and 55 females) were included in the study. Mostly used analgesic was Diclofenac (71.9%) and Paracetamol (45.8%) and preferred routes was parenteral over enteral. IM was most preferred (51%).Dosage regimen adjustment was done only in 6.25% of patients. Even after taking medication 61.5% experienced moderate pain and only 3.1% was completely relieved from pain. The quality of pain therapy as per patient response was found that 85.4% of them gave excellent response. Conclusion: This study showed various analgesics prescribed for patients who underwent different surgical procedures. Diclofenac was mainly used for pain treatment followed by Paracetamol. Both parenteral and enteral routes were used. Early modifications in therapy according to patient’s needs and
Keywords: Pain management; Post-surgery; Analgesic; Dosage regimen adjustment; Pain scale.